Seasonal variability of epipelic microphytobenthos community in two subtidal areas of the Northern Adriatic Sea - MULE, APURVA; NERI, FRANCESCA; ROMAGNOLI, TIZIANA; ACCORONI, STEFANO; CARIDI, FRANCESCA; CAMPANELLI, ALESSANDRA; UBALDI, MARIKA; SARNO, DIANA; TOTTI, CECILIA (Mediterranean Marine Science, 2024)
We investigated the biodiversity and seasonality of subtidal benthic diatoms at two sites of the Northern Adriatic Sea differently affected by anthropogenic inputs. Sediment samples were collected seasonally, and diatom cells were then separated from the sediment using the density gradient centrifugation method. The total abundance of benthic diatoms ranged between 4,409 ± 1,638 and 77,663 ± 30,415 cells cm-2 and the biomass between 0.41 ± 0.22 and 3.66 ± 2.01 μg C cm-2. At both stations, the benthic diatoms showed a marked seasonal pattern, with maximum abundance, biomass and biodiversity in spring and minimum in summer. Motile life forms, such as Navicula, Nitzschia, Fallacia, and Psammodictyon, dominated in terms of abundance at both stations throughout the study period, while plocon (centric diatoms mainly belonging to Biddulphiaceae) increased under mixing conditions, when they represented the largest contributor to biomass. At both stations and in all seasons, the Si:N:P ratio highlighted the strong P limitation, typical of the Adriatic Sea. The ammonium concentration was the highest component of DIN in spring and summer when we observed the highest and lowest MPB abundance respectively. The preference of diatoms for ammonia, coupled with the increased daylight period, may have enhanced the spring growth, whereas in summer the hypoxic conditions may have caused a decrease. Despite the different environmental conditions, the two stations exhibited similar species compositions and seasonal trends, highlighting relative stability against anthropogenic pressures of a different nature.